LEGAL PROTECTION AGAINST CONSUMERS IN E-COMMERCE TRANSACTION - Muljono, Bambang Eko; Sastradinata, Dhevi Nayasari; Nahdliyah, Hadziqotun; Putri Ayu Wangi, Yasmin Pinasti (Jurnal Independent, 2022)
Abstraction With the characteristics of e-commerce like this, consumers will face various legal problems and the current legal protection regulations for consumers have not been able to protect consumer rights in cross-border e-commerce transactions in Indonesia. In e-commerce transactions, there are no more country boundaries, so the consumer protection laws of each country like Indonesia's will not be enough to help, because e-commerce operates across borders. In this connection, legal protection for consumer rights must be carried out with an international approach through harmonization of law and cooperation with law enforcement institutions. In 2008, the Indonesian government issued Law of the Republic of Indonesia Number 11 of 2008 concerning Information and Electronic Transactions. In this Law on Information and Electronic Transactions, it is regulated regarding electronic transactions, one of which is activities regarding buying and selling in this internet media.